PENGARUH KUALITAS MANAJEMEN LINGKUNGAN TERHADAP KEUNGGULAN BERSAING PADA INDUSTRI MANUFAKTUR DI JAWA TENGAH - Cahyono, Budhi; Sulistyo, Heru (JURNAL BISNIS STRATEGI, 2002)
Quality revolution programs have position quality as main object. Corporates focus on continuous improvement and how to create cus tomer satisfaction continually. The other side, Berry and Rondinelli (1998) say that in the twenty first century indicated as a new revolution industry, especially in environmental management. This fact have make corporates must redefinition to their object, they not only exploiting human resources and natural resources, but also how they must responsibility to environ mental.This research is design to know the impact of Quality environmental management (OEM) practices to competitive advantage. The first hypoth esis focus the impact OEM on competitive advantage and the second hypothesis emphazises the impact of interaction OEM with corporate performance as moderating variable on competitive advantage. Data was collected by mail survey with object corporates that resistance on envi ronmental problem. Population are all corporate that resistance to envi ronmental problem and the research variabel are : quality environmental management, corporate performance and competitive advantage. Respond rate from quesionare that mailed reach 28% from total popula tion 150 corporates. All item in three variabel were measured by 5 point Ukertscale (strongly disagre to strongly agree) and all items were valid. By alpha cronbach, all variables indicate reliable (OEM 0, 7789, GP = 0, 8433, CA  = 0, 7827). This resuit indicate that quality environmental management has positive impact on competitive advantage. The other result indicate that interaction quality environment management and corporate performance (as moderating variable) has positive impact on competitive advantage